(untitled) (Architecture Image Studies, 2025)
This study aims to examine the impact of implementing map-based worksheets on students’ spatial thinking skills in Social Studies (IPS). The method used was quantitative with a two-group post-test only experimental design. This study was conducted at SMP Plus Al Fatimah Bojonegoro, Indonesia. The study sample consisted of two groups: an experimental group that used map-based worksheets and a control group that was not given the treatment. Data were collected through spatial thinking tests administered before and after the implementation of map-based worksheets. The results of the analysis using the Independent t-test showed a significant difference between the experimental and control groups (p = 0.002), with the experimental group showing a better increase in spatial thinking skills. The validity and reliability of the instruments used in this study also showed excellent results, and the prerequisite tests (normality and homogeneity of variance) met the requirements for the Independent t-test. This study concludes that the implementation of map-based worksheets is effective in improving students’ spatial thinking skills in IPS learning, and it is recommended to implement it more widely in learning at school.